Multi-isocentric volumetric arc-based total body irradiation: radiation dose impact on oncological outcomes in patients receiving allogeneic hematopoietic cell transplantation - Romanowska, Anna; Kamińska, Joanna; Sadowska-Klasa, Alicja; Prawdzik–Dampc, Anita; Zaucha, Renata (Frontiers in Oncology, 2026)
Background and purposeTotal body irradiation (TBI) is an important component of conditioning schedules. Data comparing different radiotherapy (RT) regimens in allogeneic hematopoietic cell transplantation (allo-HCT) remain limited. We aimed to evaluate the oncological outcomes of patients receiving different RT doses.Materials and methodsAll patients treated with multi-isocentric volumetric arc-based total body irradiation (VMAT-TBI) at a dose of ≥8 Grays (Gy) between 2021 and 2023 were included in this retrospective analysis. The RT regimens were either 8 Gy delivered in 4 bi-daily fractions (fx) or 12 Gy in 6 bi-daily fx. We evaluated the overall survival (OS), relapse-free survival (RFS), engraftment, and toxicities in both groups.ResultsForty-two patients met the inclusion criteria, including 24 treated with a 12 Gy regimen. Hazard ratio for OS after adjusting for age, Charlson Comorbidity Index (CCI), Disease Risk Index (DRI), disease status and total conditioning score (TCI) for survival was 0.02 (0.00, 0.48. p=0.01) in favor of a higher dose. The median RFS in the 12 Gy cohort was not achieved, and it was 11.8 months in the 8 Gy group. Toxicities were comparable between the groups. Two treatment-related deaths occurred in the 8 Gy arm. All patients in the 12 Gy arm achieved engraftment, whereas one graft failure was observed in the 8 Gy arm.ConclusionIn patients receiving modern TBI before allo-HCT with high-quality dose distribution, 12 Gy appears to be more effective than 8 Gy. However, this concerns a single-center cohort with TBI dose allocation according to estimated patient fragility before transplant. Therefore, randomized trials are required to determine the optimal RT dose.